Psychology in the country of the future: The VI Interamerican Congress of Psychology (Rio de Janeiro, 1959) - Degani-Carneiro, Filipe; Jacó-Vilela, Ana Maria; Amaral do Espírito-Santo, Adriana; Goulart Naves Trevisan Vasconcellos, Maira Allucham (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
This article analyses the historical conditions and effects of the VI Interamerican Congress of Psychology (VI ICP) held in Rio de Janeiro (1959). During the late 1950s, Brazil was going through a period of economic and cultural developmental euphoria and the emergence of a new image of Brazil to the world. It was also a period marked by the creation of the first undergraduate courses in Psychology (starting in 1953), as well as by the political negotiations that culminated in the legal regulation of the psychology profession (1962). The sources consulted were the Annals of the VI ICP, containing lists of participants and abstracts of the papers presented, as well as press publications that portrayed the media coverage of the congress. The VI ICP had an attendance of 409 persons from 13 countries, 254 women and 151 men, plus 4 unidentified people. The VI ICP was a milestone of impulse for Psychology as an emerging profession in Brazil, while the public repercussion of the event contributed both to the visibility of this science in the domestic environment and to the dissemination of the Brazilian psychological production at the continental level.